2017
DOI: 10.12816/0041687
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitudes and Practices regarding Pulmonary Tuberculosis among Saudi Arabia Community in 2017

Abstract: Background: Despite the improvements in the health care education of management in KSA, the prevalence of tuberculosis remains alarming. Objectives: Evaluation of the knowledge, attitude and practice among Saudi population regarding pulmonary tuberculosis (TB) in Kingdom of Saudi Arabia (KSA). Methods: A multi-center community cross sectional study was assessed among random sample of 2056 adult Saudi subjects from different regions in KSA. All participants filled out a questionnaire that included questions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
3
9
0
Order By: Relevance
“…About 71% of the subjects in a study conducted by Tolossa D et al stated they will go to health facility for treatment. 7 Similar findings were reported by our study, Easwaran et al, Konda SG et al, Angeline GG et al, Aseeri AA et al, Solliman MA et al and Rana MM et al 9,10,5,14,15,18 Haasnoot PJ et al, reported that 72% of the subjects in their study correctly stated that tuberculosis can be treatable and 6% stated correctly that TB can be cured. 6 Kigozi et al, reported that about 96.3% of their study subjects believed that TB can be cured.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…About 71% of the subjects in a study conducted by Tolossa D et al stated they will go to health facility for treatment. 7 Similar findings were reported by our study, Easwaran et al, Konda SG et al, Angeline GG et al, Aseeri AA et al, Solliman MA et al and Rana MM et al 9,10,5,14,15,18 Haasnoot PJ et al, reported that 72% of the subjects in their study correctly stated that tuberculosis can be treatable and 6% stated correctly that TB can be cured. 6 Kigozi et al, reported that about 96.3% of their study subjects believed that TB can be cured.…”
Section: Resultssupporting
confidence: 88%
“…The most common symptom stated was cough with expectoration (51.33%) in our study. 7,10,11,5,14,17,18 Hibstu DT et al, conducted a study to assess knowledge among school students in their area about TB and found that 59.8% had good knowledge about the cause and transmission of the disease. 12 Another study conducted by Howley MM et al, among the whites and blacks in the US reported that the white participants had higher knowledge score about the cause, transmission and clinical presentation of TB when compared to black participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The negative attitude was reported as majority thought they will not suffer from TB, feel fears towards TB and less than half would search for treatment. Of the respondents, 42.3% would avoid people with TB and 29.9% of respondents actually have fear towards them ( 25 ). An interventional study done in Iran regarding the effectiveness of TB health education suggested that interventions should focus on the culture and beliefs of a population in order to improve and to maintain positive attitudes.…”
Section: Discussionmentioning
confidence: 99%